Evidentiary Legal Aspects of Oral Defamation Committed in Public: A Study of Amlapura District Court Decision Number Nomor 64/Pid.B/2020/PN Amp - Armando, Fadli; Risdalina, Risdalina; Kusno, Kusno (CV. Social Politic Genius (SIGn), 2025)
The striking disparity between the Defendant’s resistance and the judge’s mitigating considerations in an oral defamation case constitutes a juridical anomaly. This condition fundamentally undermines legal certainty and the victim’s sense of justice. This research conducts a juridical review of Decision Number 64/Pid.B/2020/PN Amp. In said decision, the judge imposed a conditional sentence (probation) on a Defendant who, based on the evidence, was found to have refused to apologize to the victim. This research aims to analyze the evidentiary legal aspects in the fulfillment of the objective and subjective elements of the offense, as well as to test the validity of applying the conditional criminal sanction based on trial facts. The research method applied is normative legal research with a case approach and a statute approach to dissect the coherence between facts and norms. The results reveal a dualism in the quality of law enforcement. At the stage of proving guilt, the Panel of Judges successfully proved all elements of Article 310 section (1) of the Penal Code precisely based on valid evidence under Article 184 of the Criminal Procedure Code. However, at the sentencing stage, the application of Article 14a of the Penal Code involves a serious internal logical defect (an internal contradiction). The material requirement of “behavioral prognosis” was based on assumptions of imaginary remorse and is opposed to the trial facts demonstrating a high degree of defiance. In conclusion, this decision contains an inconsistency in proving the subjective requirement, implying a high risk of supervision execution failure as stipulated in Article 276 of the Criminal Procedure Code. The research recommends the necessity for objectivity in remorse indicators within sentencing guidelines to prevent veiled impunity and maintain judicial authority.